2019
DOI: 10.1002/nau.24032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early intravesical administration of resiniferatoxin to spinal cord‐injured rats in neurogenic detrusor overactivity

Abstract: Objectives To investigate if intravesical administration during spinal shock of resiniferatoxin (RTX), an ultrapotent desensitizing agonist of transient receptor potential vanilloid‐1 (TRPV1), would silence TRPV1‐expressing bladder afferents at an early stage of disease progression and modulate neurogenic detrusor overactivity (NDO) emergence. Materials and Methods Rats submitted to largely incomplete spinal cord transection at T8/9 spinal segment were treated with intravesical RTX (50 nM) or its vehicle durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
2
16
1
2
Order By: Relevance
“…Previous studies assessing animals submitted to complete spinal cord transection have demonstrated that post-SCI urinary impairment courses with axonal sprouting of sensory afferents at the lumbosacral spinal cord [ 42 , 45 ]. To confirm whether the SCI-induced bladder dysfunction observed here was also linked to sprouting of the central processes of sensory afferents, levels of GAP43, an established marker of axonal sprouting [ 46 ], were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies assessing animals submitted to complete spinal cord transection have demonstrated that post-SCI urinary impairment courses with axonal sprouting of sensory afferents at the lumbosacral spinal cord [ 42 , 45 ]. To confirm whether the SCI-induced bladder dysfunction observed here was also linked to sprouting of the central processes of sensory afferents, levels of GAP43, an established marker of axonal sprouting [ 46 ], were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Shimura et al [ 23 ] reported that upregulated TRPV1 in urothelial cells of patients with lower urinary tract symptoms is positively correlated with urgency urinary incontinence and reflects the severity of OAB. Reduction of bladder TRPV1 expression by early intravesical administration of TRPV1 desensitizing agonist after spinal cord injury has been shown to improve bladder function in neurogenic rats with DO, with a decrease in intravesical pressure and amplitude of bladder contractions [ 24 ]. Although other studies have shown that TRPV1 expression is higher in patients with idiopathic OAB than in healthy controls [ 5 25 ], we did not find a relationship between TRPV1 and urgency in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ekkor főként a TRPV1-és TRPV4-receptor-altípusok fokozott expressziója mutatható ki, aminek szerepe lehet a húgyhólyagban bekövetkező megnyúlás fokozott szenzoros érzékelésében [26]. A TRPV-receptorok kapszaicinnel történő gátlása révén sikerült a kóros vizelési reflexműködéseket mérsékelni [27,28], részben a C-afferensekhez kötődő idegvégződések neuropeptidszintjének csökkenését [29], részben pedig a TRPV1-receptorok deszenzitizációját, illetve roncsolását feltételezve a kedvező hatások hátterében [30,31], mely hatások reziniferatoxinnal is kiválhatók [32][33][34]. A jelenlegi gyakorlatban a motoros működések botulinumtoxin intravesicalis alkalmazása révén befolyásolhatók, melynek hatása a preszinaptikus acetil-kolinfelszabadulás gátlásán keresztül valósul meg, a cisztometriás kapacitás növelése és az inkontinens epizódok számának, illetve a detrusornyomásnak a csökkentése révén [35][36].…”
Section: A Vizelési Reflex Szenzoros éS Motoros Innervációjára Ható Kunclassified
“…Invazív kezelési módok a neurogénhólyag-szindróma kétfajta alapesetében a klinikai alkalmazás sorrendjében (a nemzetközi szakirodalom alapján összegezve [37], illetve saját klinikai tapasztalat alapján) zetközi szakirodalmi adatok szerint) kannabinoidok és szelektív szerotonin-, noradrenalinvisszavétel-gátlók is szóba jöhetnek. A vizelési reflex szenzoros ágának befolyásolását ma már nem használják (kapszaicin és reziniferatoxin révén) kevésbé kontrollálható hatásuk miatt [31][32][33][34][35]. A detrusor izom denervációja gyógyszeres terápiára rezisztens esetekben jön szóba botulinumtoxin lokális alkalmazása mellett [36].…”
Section: Táblázatunclassified